Comparison of HCG Trigger versus Dual Trigger in Improving Pregnancy Outcomes in Patients with Different Ovarian Responses: A Retrospective Study - Ke Xu; Jinrong Wang; Shuangshuang Yang; Zhenjing Wang; Ning Hou; Mei Sun (International Journal of Endocrinology)
Objective. During in vitro fertilization-embryo transfer (IVF-ET) treatment, the reproductive endocrine regulatory mechanisms hold pivotal importance. Specifically, the serum estradiol (E2) level during ovulation emerges as a critical factor influencing pregnancy outcomes. This retrospective study aimed to comprehensively compare two common clinical regimens based on the grouping of serum E2 levels and the number of oocytes retrieved on the trigger day. Our objective was to evaluate the pregnancy outcomes in IVF-ET patients across different ovarian response groups, exploring the efficacy of the dual-trigger and single-trigger regimens to provide valuable insights for optimizing clinical strategies in the context of IVF-ET. Methods. A retrospective analysis was conducted on the clinical data of 2778 infertile patients who underwent ART (IVF/ICSI). Subsequently, a detailed statistical analysis was performed on 1032 patients following an antagonist regimen. Participants were categorized into single-trigger and dual-trigger groups based on real-world trigger protocols, considering different ovarian responses. Comprehensive statistical assessments were conducted on baseline characteristics, ovulation induction, and pregnancy outcomes. Results. Baseline characteristics and cycle parameters among the three patient groups (high ovarian response, normal response, and poor response) exhibited no significant differences between the dual-trigger and single-trigger regimen groups. Despite the dual-trigger regimen utilizing a significantly lower HCG dose, no notable discrepancies were observed in laboratory results and pregnancy outcomes (embryo transfer rate, pregnancy rate, and live birth rate) for normal and high responders. Remarkably, E2 levels were higher in the dual-trigger group compared to the single-trigger group. In high and normal responders, the dual-trigger regimen demonstrated increased oocyte counts and oocyte acquisition rates, coupled with decreased transfer cancellation rates attributed to ovarian hyperstimulation syndrome (OHSS). Intriguingly, patients with a poor ovarian response experienced no graft cancellations due to OHSS prevention in either group. Conclusion. For patients with high and normal ovarian responses, the utilization of a dual-trigger regimen on the trigger day effectively mitigates the risk of OHSS. Our large sample study supports the substitutability of the dual-trigger regimen over the single-trigger regimen without compromising pregnancy outcomes. However, this conclusion is not applicable to patients with poor ovarian responses. The results of this study highlight the necessity of adopting a customized and individualized treatment approach that should be based on the patient’s ovarian response. Additionally, recognizing the pivotal role of the endocrine environment in influencing pregnancy outcomes and the occurrence of OHSS, further exploration of the effects of different triggering regimens on endocrine parameters is warranted. Such investigations will contribute to enhancing the reproductive outcomes of IVF-ET technology.